Moda e design: linguagens contemporâneas na construção teórica e crítica - Castilho, Káthia; Moura, Monica [UNESP] (My University, 2013)
This article aims to contribute to the process of constructing a scientific and critical theory from the interrelationship of design and fashion fields. Accordingly, are not only listed fashion and design issues in contemporaneity and tensions between these two fields, but also stated the language aspects of these two areas. We hope that the approach and the issues addressed here can contribute and collaborate on research studies, discussions and reflections that lead to the deepening of these relations in the constitution of a fashion and design theory.

Esse artigo tem como proposta colaborar para o processo de construção de uma teoria científica e crítica a partir da inter-relação dos campos do design e da moda. Nesse sentido, elenca as questões da moda e do design no contemporâneo, as tensões existentes entre esses dois campos e apresenta os aspectos de linguagem destas duas áreas. Esperamos que o enfoque e as questões aqui tratadas possam contribuir e colaborar com estudos, pesquisas, discussões e reflexões que levem ao aprofundamento dessas relações na constituição de uma teoria da moda e do design.
Fashion and design: contemporary languages in theoretical and critical construct
Keywords: Fashion; Design; Language; Theory; Criticism; Moda; Design; Linguagem; Teoria; Crítica